Application of the Team Games Tournament (TGT) Model to Improve Biology Learning Outcomes at SMAN 1 Sultan Daulat - Sariati; Elfrida; Rita Mahyuny, Siska (Bioilmi: Jurnal Pendidikan, 2024)
One of the obstacles in the learning process at SMAN 1 Sultan Daulat is that some students have low interest in learning. This is thought to be due to the lack of variations in learning models, so that the percentage of students who achieve the KKM score is only 65%. This research aims to determine the improvement in student learning outcomes by implementing the Team Games Tournament model. This research is quantitative research. The population in this study were all class XI students of SMAN 1 Sultan Daulat, totaling 46 students. The sample used was class XI Science 1. The data collection technique for the learning outcomes test was in the form of multiple choice. The data analysis technique was carried out quantitatively, namely by hypothesis testing and N-gain testing. The results of the research show that there is an increase in student learning outcomes based on the results of hypothesis testing with tcount > ttable, namely 18.25 > 2.074 at a significance level of 5%. The increase in student learning outcomes can be seen from the average normalized N-gain result of 0.67 with the criteria for increasing learning outcomes being 67% in the medium category. Thus, the hypothesis in the research was accepted and it was concluded that there was a significant increase in student learning outcomes from implementing the Team Games Tournament model.